Nudging digital physical activity breaks for home studying of university students—A randomized controlled trial during the COVID-19 pandemic with daily activity measures - Teuber, Monika; Leyhr, Daniel; Moll, Juliane; Sudeck, Gorden (Frontiers in Sports and Active Living, 2022)
University students are of particular public health interest because they are at high risk for physical inactivity and sedentary behaviors. In conjunction with the COVID-19 pandemic, sedentariness and physical inactivity were reinforced, as the pandemic led to an increase in home studying. Physical activity (PA) breaks have been identified as promoting factors for university students' physical and mental health. Therefore, the present study explored an approach to nudge students to take PA breaks at home while studying. The purpose was to test the effectiveness of digital nudging for PA breaks for 10 days using a randomized intervention design during the COVID-19 pandemic. It included an intervention group who received daily digital motivational prompts for PA break videos and a minimal intervention control group who got low-level access to PA break videos via a one-time link sent to the media library. Using a sample of university students in the southwest of Germany (n = 57), two-level binary logistic regression models were calculated to predict daily participation in PA breaks during the intervention period depending on the nudging intervention, as well as previous participation in PA breaks, the general PA level of the subjects before the intervention, the time spent on PA and on home studying in a day, the kind of day during the intervention (weekday vs. weekend), and the students' age. Results revealed that the digital nudging intervention did not show any significant effect on the likelihood to participate in PA breaks on a given day (0.69 ≤ β ≤ 0.75, p > 0.3). Instead, an individual-level effect revealed that the longer a student studied at home over the course of a day, the more likely he or she was to take a PA break (1.07 ≤ β ≤ 1.11, p < 0.001). Current findings show that individual characteristics such as daily time spent on home studying, which can change over the course of the intervention phase, are relevant considerations within nudging intervention in university setting. This provides initial insights especially for digital PA breaks for students during home studying.